Impact of shrinkage on crack width and deflections of reinforced concrete beams with and without steel fibres. (15th February 2019) - Al-Kamyani, Zahran; Guadagnini, Maurizio; Pilakoutas, Kypros
Highlights: Shrinkage in RC should be accounted for in short-term crack widths predictions. Propose a method that accounts for nonuniform shrinkage in crack widths predictions. Shrinkage has major influence in beams deflections at service loads. Blends of manufactured and recycled steel fibres reduce crack widths effectively. Abstract: Current recommendations by fib Model Code 2010 only consider the effect of shrinkage strains on long-term crack width calculations of reinforced concrete (RC) elements. However, shrinkage strains develop fairly early and can influence mean strains as well as short-term crack width and deflection calculations. This paper examines the effect of shrinkage strains on short-term deformations using experiments on eight RC beams, with and without steel fibres, at the age of 4–5 months. The results show that due to shrinkage, measured strains, deflections and crack widths are higher than expected for fully cracked sections. The MC-2010 predictive equation for crack widths is amended to account for shrinkage strains and induced curvatures. This work will lead to better design equations and less serviceability problems in RC structures.